Study protocol of an open-label prospective phase II umbrella study of precise neoadjuvant therapy for patients with stage II-IIIB resectable non-small cell lung cancer (PURPOSE) - Wang, Yiyang; Zhai, Haoran; Wang, Jiaming; Mao, Teng; Ji, Chunyu; Bao, Feichao; Gu, Zhitao; Fang, Wentao (Frontiers in Oncology, 2022)
Background The outcomes of locally advanced non-small cell lung cancer (LA-NSCLC) are unfavorable mainly due to a high risk of cancer recurrence. Only around 5% of patients can benefit from perioperative chemotherapy which is the current standard treatment. Recently, promising results with neoadjuvant targeted and immunotherapy therapy have been seen. However, most clinical trials are looking for patients eligible for certain drugs, instead of seeking suitable treatments for certain patients. Therefore, it is necessary to look for more efficient perioperative therapies to increase resectability, reduce recurrence and improve prognosis. Methods/Design The study is an open-label, prospective, phase II, umbrella trial, enrolling patients diagnosed with treatment-naïve potentially resectable Stage II-IIIB NSCLC. Next-generation sequencing (NGS) using a 68-gene panel is performed for biopsies of tumor tissues from eligible patients. Enrolled patients are then stratified into six independent cohorts based on the status of gene mutations and PD-L1 status in tumor tissues, that is, ①EGFR 19del group, ②EGFR 21 L858R group, ③EGFR rare mutation group, ④Other driver mutation group, ⑤Drive mutation-negative group with PD-L1≥1%, ⑥Drive mutation-negative group with PD-L1<1%. A Simon’s two-stage design is performed in each cohort independently and patients receive corresponding standard therapies accordingly. We aim to enroll 26 patients in each cohort and totally 156 patients will be enrolled. The primary endpoint is objective response rate (ORR). Secondary endpoints include oncological prognosis and perioperative outcomes. Exploratory endpoint is to investigate patient-specific minimal residual disease (MRD) in predicting treatment efficacy and oncological prognosis. Discussions This is the first umbrella trial focusing on the safety and efficacy of precise neoadjuvant therapy for patients diagnosed with potentially resectable LA-NSCLC based on NGS results. The results of this trial would help improve overall treatment results in LA-NSCLC patients. Trial Registration: Chinese Clinical Trial Registry. Trial registration number: ChiCTR2100053021. Advantages and Limitations of this Study: There is no neoadjuvant umbrella trial focusing on LA-NSCLCs. This is the first neoadjuvant umbrella trial, using a precise individualized approach and seeking suitable drugs for LA-NSCLC patients, with the aim to improve overall treatment outcomes. Clinical Trial Registration: https://www.chictr.org.cn/, identifier ChiCTR2100053021.